AHMAD MARZUQI AL-BĀTĀWĪ’S THOUGHTS IN FAḌL AL-RAḤMĀN BOOK AND ITS IMPLEMENTATION ON DETERMINING ISLAMIC CALENDAR IN INDONESIA - Yaqin, Ahmad Ainul; Rohman, Khabib Syaikhu; Faza, Ricka Ulfatul (Al-Hilal: Journal of Islamic Astronomy, 2023)
Criteria for the visibility of the new moon have been initiated by Betawi ulama, one of which is found in the book Faḍl al-Raḥmān by Ahmad Marzuqi al-Bātāwī. Ahmad Marzuqi's criteria are very different from those used by the Indonesian Ministry of Religion, giving rise to several differences. Using literature research and interviews as a data collection method, this paper finds that Ahmad Marzuqi al-Bātāwī's thoughts in the book Faḍl al-Raḥmān state that the minimum limit for imkān al-rukyah is 7° without using a telescope. This idea of imkān al-rukyah is still currently being implemented by the al-Marzūqiyyah congregation in Cipinang Muara, East Jakarta, in determining the start of the lunar month so that if the height of the new moon is less than 7° it causes differences with the government.